Prevalence of Microorganisms and Antibiotic Sensitivity Among Patients with Diabetic Foot Ulcer in Sulaimani City, Iraq - Aso Qadir; Bakhtiar Mahmoud; Taha Mahwi; Delman Mohammed Raoof Arif Al-Attar; Safeen Othman Mahmood (Baqiyatallah University of Medical Sciences, 2020)
Background: Diabetic foot ulcers (DFUs) are responsible for days of costly hospitalization and are the major cause of medical lower limb amputations. Determining the appropriate antimicrobial therapy for DFUs is highly dependent on recognizing the microorganisms that cause them. Many reports have indicated that there has been a remarkable increase in antibiotic resistance. Objectives: The present study examined various cultures of patients with DFUs to detect the prevalence of microorganisms and their antibiotic sensitivity profiles. Methods: This cross-sectional study was carried out on 92 patients with DFUs admitted to Shar Teaching Hospital and Shahid Hemin Teaching Hospital. Wagner Classification was used to assess the severity and location of the DFUs. Patients were asked questions about their practices of foot care and hygiene, and their answers were recorded. Samples required for testing were taken using sterile swabs. Results: A total of 100 microorganisms were isolated from 92 patients with DFUs, 10 of which were polymicrobial and 2 were culture-negative. There was a highly significant association between the isolated gram-negative microorganisms and higher grades of DFU (P < 0.001). A highly significant association was also observed between bad patient knowledge of hygiene practices and gram-negative microorganisms (P < 0.001). Osteomyelitis was present in 40 (43.4%) patients. Conclusion: Among gram-positive and gram-negative bacteria, Staphylococcus spp. and E. coli were, respectively, the most frequent organisms isolated. The antibiotic imipenem was found to be effective against microorganisms. Tetracycline, erythromycin, and ceftriaxone, however, were highly resistant to antibiotics. To sum up, since different microorganisms are involved and multidrug-resistant strains might emerge, clinicians are recommended to take cultures into account before they initiate empirical therapy.